Workplace Segregation in the United States: Race, Ethnicity, and Skill - Hellerstein, Judith K.; Neumark, David (The Review of Economics and Statistics, 2008)
We study workplace segregation in the United States using a unique matched employer-employee data set that we have created. We present measures of workplace segregation by education and language, and by race and ethnicity, and we assess the role of education- and language-related skill differentials in generating workplace segregation by race and (Hispanic) ethnicity. Our results indicate that there is considerable segregation by race, ethnicity, education, and language in the workplace. Only a tiny portion of racial segregation in the workplace is driven by education differences between blacks and whites, but a substantial fraction of ethnic segregation in the workplace can be attributed to differences in English-language proficiency. Finally, additional evidence suggests that segregation by language likely reflects complementarity among workers speaking the same language.